2017
DOI: 10.1038/bjc.2017.175
|View full text |Cite
|
Sign up to set email alerts
|

Potentiating the effects of radiotherapy in rectal cancer: the role of aspirin, statins and metformin as adjuncts to therapy

Abstract: Background:Complete tumour response (pCR) to neo-adjuvant chemo-radiotherapy for rectal cancer is associated with a reduction in local recurrence and improved disease-free and overall survival, but is achieved in only 20–30% of patients. Drug repurposing for anti-cancer treatments is gaining momentum, but the potential of such drugs as adjuncts, to increase tumour response to chemo-radiotherapy in rectal cancer, is only just beginning to be recognised.Methods:A systematic literature search was conducted and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 92 publications
1
29
0
Order By: Relevance
“…Regarding prevention, evidence for a role for statins is perhaps strongest for gastric, esophageal, liver and colorectal cancer, but some studies suggest roles for certain hematologic, lung and pancreatic malignancies . Regarding cancer recurrence and progression, a role for statins as an adjunct therapy has been suggested for breast, colorectal and rectal cancers …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding prevention, evidence for a role for statins is perhaps strongest for gastric, esophageal, liver and colorectal cancer, but some studies suggest roles for certain hematologic, lung and pancreatic malignancies . Regarding cancer recurrence and progression, a role for statins as an adjunct therapy has been suggested for breast, colorectal and rectal cancers …”
Section: Discussionmentioning
confidence: 99%
“…Besides prevention of cardiovascular disease (CVD), statins could impact cancer occurrence or progression based upon cholesterol's role as a precursor of steroid hormones synthesis, activator of the inflammasome, and its involvement in cellular homeostasis and the biologic function of cell membranes. Studies have addressed use of statins as an adjunct to initial chemotherapy or radiotherapy, in reducing the risk of recurrence, or as a chemo‐preventive agent for several types of cancers including colorectal, esophageal, gastric, and liver …”
Section: Introductionmentioning
confidence: 99%
“…Other agreements between model predictions and experimental studies include implication of inflammation-mediating eicosanoids in radiation resistance. Many prostaglandin metabolites identified in this study have previous associations with radiation resistance, and cyclooxygenase inhibitors such as aspirin may act as radiation sensitizers and improve outcomes in cervical, prostate, and rectal cancers 45,[56][57][58] . These findings suggest that lipid and eicosanoid metabolites may have utility as both diagnostic biomarkers as well as therapeutic targets for improving radiation response.…”
Section: Non-invasive Classifier Implicates Blood Metabolic Featuresmentioning
confidence: 79%
“…A recent review reported promising results for statins and aspirin in increasing the response to chemoradiotherapy in patients with rectal cancer. [38] However, any new drugs given to patients already burdened by a diagnosis of cancer, radiotherapy treatment and the side effects of long course chemotherapy need to have proven efficacy. Randomized controlled trials investigating the drugs singularly or in combination to determine whether they confer an increase in response to chemo-radiotherapy are needed.…”
Section: Discussionmentioning
confidence: 99%